Determination of median lethal concentration of two common heavy metal pollutants in rivers, potassium chromate and cadmium nitrate, to red zebrafish and their mortality causes. Issue 1 (November 2020) - Liu, Yipeng; He, Zhonghao; Ye, Jiyang; Zheng, Yan; Huang, Ziqi; Yan, Yibo
Abstract: In order to investigate the toxicological properties of river pollutants, potassium chromate (K2 CrO4 ) and cadmium nitrate tetrahydrate (Cd (NO3 )2 ·4H2 O) were selected as they are commonly discharged from industry to nearby rivers. This paper studied the Median Lethal Concentration (LC50 ) of the pollutants to the adult red zebrafish by acute toxicity experiments within 96 hours. 120mg/L, 130mg/L, 140mg/L, 150mg/L, 160mg/L, 170mg/L potassium chromate solutions and 16mg/L, 20mg/L, 24mg/L, 28mg/L 32mg/L, 36mg/L cadmium nitrate tetrahydrate solutions were prepared with triplicates to determine the LC50 . The results of the preliminary experiments and the calibration curves suggested that the LC50 of potassium chromate and cadmium nitrate tetrahydrate were 165 mg/L and 28 mg/L respectively. The toxicity of thresholds and LC100 were also evaluated. Through the observations of the tested subjects in morphological, ethological and anatomical manners, behavioural alterations, oxidative stress, and immunotoxicity were probably their major causes of death.